The economic burden of cancer, coronary heart disease, dementia and stroke in England in 2018: an evaluation of two cohort studies - Landeiro, F; Harris, C; O'Neill, S; Jandu, KS; Tacconi, EMC; Field, S; Patel, N; Gopfert, A; Hagson, H; Leal, J; Luengo-Fernandez, R; Groves, D (Elsevier, 2024)
Background: Cancer, coronary heart disease, dementia, and stroke are major contributors to morbidity and mortality in England. We aimed to assess the economic burden (including health-care, social care, and informal care costs, as well as productivity losses) of these four conditions in England in 2018, and forecast this cost to 2050 using population projections. Methods: We used individual patient-level data from the Clinical Practice Research Datalink (CPRD) Aurum, which contains primary care electronic health records of patients from 738 general practices in England, to calculate health-care and residential and nursing home resource use, and data from the English Longitudinal Study on Ageing (ELSA) to calculate informal and formal care costs. From CPRD Aurum, we included patients registered on Jan 1, 2018, in a CPRD general practice with Hospital Episode Statistics (HES)-linked records, omitting all children younger than 1 year. From ELSA, we included data collected from wave 9 (2018–19). Aggregate English resource use data on morbidity, mortality, and health-care, social care, and informal care were obtained and apportioned, using multivariable regression analyses, to cancer, coronary heart disease, dementia, and stroke. Findings: We included 4 161 558 patients from CPRD Aurum with HES-linked data (mean age 41 years [SD 23], with 2 079 679 [50·0%] men and 2 081 879 [50·0%] women) and 8736 patients in ELSA (68 years [11], with 4882 [55·9 %] men and 3854 [44·1%] women). In 2018, the total cost was £18·9 billion (95% CI 18·4–19·4) for cancer, £12·7 billion (12·3–13·0) for coronary heart disease, £11·7 billion (9·6–12·7) for dementia, and £8·6 billion (8·2–9·0) for stroke. Using 2050 English population projections, we estimated that costs would rise by 40% (39–41) for cancer, 54% (53–55) for coronary heart disease, 100% (97–102) for dementia, and 85% (84–86) for stroke, for a total of £26·5 billion (25·7–27·3), £19·6 billion (18·9–20·2), £23·5 billion (19·3–25·3), and £16·0 billion (15·3–16·6), respectively. Interpretation: This study provides contemporary estimates of the wide-ranging impact of the most important chronic conditions on all aspects of the economy in England. The data will help to inform evidence-based polices to reduce the impact of chronic disease, promoting care access, better health outcomes, and economic sustainability. Funding: Alzheimer's Research UK.